Text Corpus Formation for the Comparative Analysis of Educational Views of H.Mann and K.Ushynsky - Vakhovskyi, Maksym (Pedagogical Discourse, 2013)
The article provides the basic principles of text corpus formation to carry out a comparative analysis of the views of the American educator and educational activist Horace Mann and the outstanding national educator Konstantin Ushynskyi. Educational activity of H. Mann and K. Ushynsky are from the same historical period, and their pedagogical ideas have a lot in common. Therefore, a comparative analysis of American and Ukrainian researchers will help with better understanding of the characteristics of schooling and educational thought in the USA and Ukraine. The article shows that the text corpus as an information system is characterized by such features as representativeness, volume and annotation. It is proved that at a stage of formation of a corpus it is necessary to ensure that the selected pedagogical texts correspond with the key range of problems, in the context of which the units of comparative analysis are singled out. The corpus of texts includes The Twelve Annual Reports to the Massachusetts Board of Education, prepared by Horace Mann in 1837-1848, as well as the articles and fundamental works of Konstantin Ushynskyi that are comparable and sufficient in volume that allows results of the comparative analysis to be accurate and trustworthy.